Photocatalytic hydrogel based on zinc oxide-chitosan as well as preparation method and application of photocatalytic hydrogel

Preparation of zinc oxide-chitosan photocatalytic hydrogels by one-step hydrothermal reaction method solves the problem of low efficiency of existing photocatalysts to remove organic pollutants in water, achieves efficient photocatalytic degradation, and the preparation process is green, suitable for the use of green Mass production.

CN119406450APending Publication Date: 2025-02-11SHANDONG UNIV +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411531672.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing photocatalysts are less efficient in removing organic pollutants in water, and the preparation process is not green enough.

Method used

Photocatalytic hydrogel based on zinc oxide-chitosan was prepared by one-step hydrothermal reaction method. ZnO nanoparticles were anchored by the coordinated-NH2 group in chitosan and protected from surface passivation. to make uniform small-sized nanoparticles.

Benefits of technology

The photocatalytic efficiency of the photocatalyst is improved, the degradation capacity of organic pollutants is enhanced, and the preparation process is simplified, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406450A_ABST
    Figure CN119406450A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photocatalysis, in particular to photocatalytic hydrogel based on zinc oxide-chitosan as well as a preparation method and application of the photocatalytic hydrogel. The photocatalytic hydrogel takes chitosan gel as a substrate and is loaded with ZnO nanoparticles. Zn ions in the photocatalytic hydrogel are coordinated with-NH2 groups in the chitosan, and ZnO can be anchored in a chitosan gel framework. Meanwhile, based on the anchoring effect of-NH2 groups on Zn ions, ZnO particles are subjected to surface passivation protection, and then uniform and small-size nano particles grow. Compared with ZnO obtained by a common hydrothermal method, the photocatalytic hydrogel has higher photocatalytic efficiency. As a porous polymer, the chitosan gel has excellent adsorption performance; the-NH2 group in the chitosan performs passivation protection on the surface of the ZnO particles, so that electron-hole recombination can be reduced, and the photocatalytic performance is further improved; and uniform and small-sized ZnO nanoparticles have larger surface area, so that the photocatalytic performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysis, and in particular to a zinc oxide-chitosan-based photocatalytic hydrogel and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In many production activities such as textile, papermaking, rubber processing, etc., a large amount of organic pollutants will be generated. These organic pollutants discharged into the water will cause serious water pollution and the growth of pathogenic microorganisms, which seriously threatens human health. In order to solve the pollution problem, water treatment technologies such as adsorption and photocatalytic degradation methods have received widespread attention. Compared with the simple transfer of pollutants by adsorption, photocatalytic degradation can achieve non-toxic transformation of pollutants, showing unique advantages in water treatment research.

[0004] Common photocatalysts include CdS, TiO 2 , ZnO, etc., among which ZnO has attracted widespread attention due to its excellent properties including non-toxicity, environmental friendliness, high photosensitivity, antibacterial properties and low price. Generally speaking, the traditional preparation methods of ZnO are mostly through direct precipitation or hydrothermal methods by mixing zinc-containing inorganic salts and alkaline reagents. Some studies on ZnO materials have shown that the preparation method will affect the properties of the material. For example, ZnO nanoparticles prepared from different precursor materials show different photocatalytic properties. Studies have shown that microwave heating is also an effective way to improve the performance of ZnO. More research is to improve the catalytic performance through ZnO composites. Many studies have reported that ZnO composites doped with various metals (silver, gold, lead, etc.) can achieve the regulation of energy level surface electronic activity and thus adjust the catalytic activity. Other studies have shown that ZnO and two-dimensional sheet materials (such as graphene, molybdenum disulfide MoS 2 The composites of ZnO (such as hydroxyapatite, MXene materials, etc.) can improve the catalytic performance by promoting electron mobility. In addition, ZnO loaded on porous materials such as hydroxyapatite, ZIF materials, etc. can enhance the catalytic activity through adsorption-catalytic synergy. Looking at the existing exploration of ZnO materials, the focus of future research is still on the greening of the preparation process and the improvement of photocatalytic activity. Summary of the invention

[0005] In order to overcome the above problems, the present invention provides a zinc oxide-chitosan based photocatalytic hydrogel and a preparation method and application thereof.

[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides a zinc oxide-chitosan based photocatalytic hydrogel, which uses chitosan gel as a substrate and is loaded with ZnO nanoparticles.

[0008] The photocatalytic hydrogel based on zinc oxide-chitosan can be obtained by a one-step hydrothermal reaction. Zn ions react with -NH 2 The groups are coordinated and ZnO can be anchored in the chitosan gel framework.

[0009] The second aspect of the present invention provides a method for preparing the zinc oxide-chitosan based photocatalytic hydrogel according to the first aspect, comprising:

[0010] The zinc salt is dissolved in a chitosan aqueous solution, the mixed solution is added into an alkaline solution, and the mixture is heated for reaction to obtain a zinc oxide-chitosan based photocatalytic hydrogel.

[0011] The third aspect of the present invention provides the use of the zinc oxide-chitosan based photocatalytic hydrogel described in the first aspect and / or the zinc oxide-chitosan based photocatalytic hydrogel prepared by the preparation method described in the second aspect in photocatalytic degradation and removal of organic pollutants in water.

[0012] The beneficial effects of the present invention are:

[0013] (1) In the present invention, a photocatalytic hydrogel based on zinc oxide-chitosan can be obtained by a one-step hydrothermal reaction, wherein Zn ions react with -NH 2 The groups are coordinated, and ZnO can be anchored in the chitosan gel framework. 2 The anchoring effect of the chitosan group on the Zn ions, the ZnO particles are protected by surface passivation and then grow into uniform small-sized nanoparticles. Compared with the ZnO obtained by the conventional hydrothermal method, the photocatalytic hydrogel in the present invention has a more efficient photocatalytic efficiency. As a porous structure, the chitosan gel has excellent adsorption performance; secondly, the -NH 2 The surface passivation protection of the group on ZnO particles can reduce electron-hole recombination and thus improve the photocatalytic performance; furthermore, ZnO nanoparticles of uniform small size have a larger surface area, thereby improving the photocatalytic performance.

[0014] (2) In the present invention, the zinc oxide-chitosan based photocatalytic hydrogel can be obtained through a one-step hydrothermal reaction. The synthesis method is simple and convenient, easy to prepare, and suitable for scale-up synthesis and actual production application. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0016] Figure 1 Schematic diagram of the preparation process of the zinc oxide-chitosan based photocatalytic hydrogel in the present invention;

[0017] Figure 2 XRD patterns of ZnO-CTS prepared in Example 1 and ZnO prepared in Comparative Example 1;

[0018] Figure 3 a and b are AFM characterization images of ZnO prepared in Comparative Example 1 and ZnO-CTS prepared in Example 1, respectively, and c and d are particle height distributions measured along the straight lines in a and b, respectively;

[0019] Figure 4 The infrared spectra of pure CTS powder, CTS gel and ZnO-CTS gel;

[0020] Figure 5 The optimized configuration of the interaction model of different functional groups of ZnO and CTS: a is -NH 2 and ZnO; b is -COCH 3 and ZnO; c and d are -OH and ZnO at different positions; C, H, O, N and Zn atoms are represented by gray, white, red, blue and green, respectively;

[0021] Figure 6 a and b are the changes of UV absorption spectra of RhB solution in the presence of ZnO (a) and ZnO-CTS (b) respectively; c is the degradation curve (c / c 0 Plotted against illumination time), d is the corresponding kinetic fitting curve (lnc 0 / c plotted against illumination time); the insets in a and b show the color change of the RhB solution;

[0022] Figure 7 UV / visible diffuse reflectance spectra (including band gap calculation diagram) (a) and fluorescence emission spectra (b) of ZnO-CTS and ZnO samples;

[0023] Figure 8 The change of RhB residue with time when the experimental condition variables are changed in Experimental Example 2; the controlled variable in a is the change of Zn ion concentration in the CTS-Zn mixed solution; the controlled variable in b is the change of NaOH concentration; the controlled variable in c is the change of the feed volume ratio of the two precursor NaOH solutions to the CTS-Zn solution; the controlled variable in d is the change of CTS content; the inset in a shows the state of the prepared product under different Zn ion concentrations;

[0024] Fig. 9 AFM observation of the surface morphology of ZnO-CTS gel prepared with different CTS concentrations;

[0025] Fig.10 a and b are the changes of UV absorption spectra of RhB solution in the presence of ZnO-CTS gel (a) and ZnO-CTS floccules (b) respectively; c is the degradation curve (c / c 0 Plotted against illumination time), d is the corresponding kinetic fitting curve (lnc 0 / c is plotted against light exposure time). DETAILED DESCRIPTION

[0026] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0027] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0028] A first typical embodiment of the present invention provides a zinc oxide-chitosan based photocatalytic hydrogel, which uses chitosan gel as a substrate and is loaded with ZnO nanoparticles.

[0029] In one or more embodiments, the size of the ZnO nanoparticles is 2-4 nm.

[0030] Zn ions and -NH 2 The groups are coordinated and ZnO can be anchored in the chitosan gel framework.

[0031] A second typical embodiment of the present invention provides a method for preparing the zinc oxide-chitosan based photocatalytic hydrogel according to the first aspect, comprising:

[0032] The zinc salt is dissolved in a chitosan aqueous solution, the mixed solution is added into an alkaline solution, and the mixture is heated for reaction to obtain a zinc oxide-chitosan based photocatalytic hydrogel.

[0033] In one or more embodiments, the zinc salt comprises Zn(CH 3 COO 2 .

[0034] In one or more embodiments, the concentration of chitosan in the chitosan aqueous solution is 1-2 wt %, preferably 1 wt %.

[0035] In one or more embodiments, the concentration of the zinc salt in the mixed solution is 0.1 to 0.4 mol / L, preferably 0.1 mol / L.

[0036] In one or more embodiments, the alkaline solution includes a NaOH solution.

[0037] Preferably, the concentration of the NaOH solution is 0.2-0.4 mol / L, preferably 0.2 mol / L.

[0038] More preferably, the volume ratio of the NaOH solution to the mixed solution is 2:1 to 5:1, preferably 4:1 or 5:1.

[0039] In one or more embodiments, the temperature of the heating reaction is 95 to 105° C., preferably 100° C.; the time of the heating reaction is 1 to 2 hours, preferably 1 hour.

[0040] In the present invention, a photocatalytic hydrogel based on zinc oxide-chitosan can be obtained by a one-step hydrothermal reaction, wherein Zn ions react with -NH 2 The groups are coordinated, and ZnO can be anchored in the chitosan gel framework. 2 Due to the anchoring effect of the groups on Zn ions, the ZnO particles are protected by surface passivation and then grow into nanoparticles of uniform small size.

[0041] A third typical embodiment of the present invention provides the use of the zinc oxide-chitosan based photocatalytic hydrogel described in the first aspect and / or the zinc oxide-chitosan based photocatalytic hydrogel prepared by the preparation method described in the second aspect in photocatalytic degradation and removal of organic pollutants in water.

[0042] In one or more embodiments, the organic pollutant comprises an organic dye, and the organic dye comprises Rhodamine B.

[0043] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0044] In the following examples, chitosan (abbreviated as CTS, C 6n H 11n NO 4n , medium viscosity, viscosity 200-400 mPa·s) was purchased from MacLean Reagent Company, and the molecular formula fragment is shown in Formula I.

[0045]

[0046] Zn(CH3COO) 2, NaOH and rhodamine B (RhB) were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0047] Example 1

[0048] Figure 1 Schematic diagram of the preparation process of the zinc oxide-chitosan based photocatalytic hydrogel in the present invention, refer to Figure 1 , dissolve chitosan in acetic acid-water solution (acetic acid concentration is 2wt%), stir to obtain a chitosan aqueous solution with a concentration of 2wt%, and add Zn(CH3COO) 2 Dissolved in acetic acid-water solution (acetic acid concentration is 2wt%) to obtain a zinc acetate solution with a concentration of 0.2mol / L. Take equal volumes of chitosan and zinc acetate solution and stir to obtain a CTS-Zn mixed solution. CTS 1wt%, c Zn 0.1 mol / L; take 10 mL of the mixed solution and dropwise add 50 ml of NaOH (c NaOH =0.3 mol / L) solution, the droplets immediately formed white balls, stirred for 10 minutes, and then hydrothermally reacted at 100°C for 1 hour to obtain a zinc oxide-chitosan based photocatalytic hydrogel, referred to as ZnO-CTS gel.

[0049] Comparative Example 1

[0050] 10mL Zn(CH3COO) 2 (c Zn =0.1 mol / L) and 50 mL NaOH solution (c NaOH The mixture was stirred for 10 minutes and then subjected to hydrothermal reaction at 100°C for 1 hour to obtain ZnO precipitate.

[0051] Comparative Example 2

[0052] Chitosan was dissolved in acetic acid-water solution (acetic acid concentration was 2 wt%), stirred to obtain a chitosan aqueous solution with a concentration of 2 wt%, and Zn(CH3COO) 2 Dissolved in acetic acid-water solution (acetic acid concentration is 2wt%) to obtain a zinc acetate solution with a concentration of 0.2mol / L. Take equal volumes of chitosan and zinc acetate solution and stir to obtain a CTS-Zn mixed solution. CTS 1wt%, c Zn 0.1 mol / L; take 10 mL of the mixed solution and add 50 ml of NaOH (c NaOH =0.3 mol / L) solution to form a white flocculent precipitate. After stirring for 10 minutes, the mixture was allowed to stand for 24 hours to obtain a zinc oxide-chitosan flocculent composite, referred to as ZnO-CTS flocculent.

[0053] Example 2

[0054] The ZnO-CTS gel prepared in Example 1 and the ZnO precipitate prepared in Comparative Example 1 were washed, dried, and ground to obtain powder samples, and the samples were characterized.

[0055] 2.1 Figure 2 The XRD patterns of ZnO-CTS prepared in Example 1 and ZnO prepared in Comparative Example 1 are shown in FIG. Figure 2 It can be seen that (100) was detected in both ZnO and ZnO-CTS samples. ZnO 、(002) ZnO , and (101) ZnO The characteristic peaks of ZnO indicate that sphalerite ZnO crystals were generated in both samples.

[0056] 2.2 Particle morphology was characterized by AFM, such as Figure 3 As shown. Both samples are nano-sized particles, among which the pure ZnO particles are larger and more unevenly distributed than the ZnO-CTS particles, indicating that the pure ZnO particles prepared without CTS are more likely to agglomerate. In addition, in the ZnO-CTS sample, particles were observed to grow along the fibers, indicating that when CTS exists, the ZnO particles are anchored in the CTS gel framework. The small size growth of ZnO-CTS particles should be related to this anchoring effect.

[0057] 2.3 In order to explore the loading structure in ZnO-CTS, infrared spectroscopy was performed, such as Figure 4 As shown. For comparison, pure CTS gel without Zn ions was prepared under the same concentration conditions as ZnO-CTS gel. The detected characteristic peaks of the sample are consistent with the infrared characteristic peaks of CTS in the literature. Among them, 1310-1320cm -1 Peak refers to CN stretching vibration (amide III band); 1550-1560cm -1 Peak refers to NH-bending vibration (amide II band); 1650-1655 cm -1 Peak refers to CO-stretching vibration (amide I band); 3100-3110cm -1 The broad peak refers to the NH-symmetric stretching vibration. Compared with the CTS pure powder (υN-H=1598cm -1 ) and CTS gel (υN-H=1579cm -1 ), the NH-bending vibration peak in ZnO-CTS gel blue-shifted to 1576 cm -1 , indicating the binding effect of Zn ions with -NH- groups, which may be the main source of the anchoring effect of CTS on ZnO.

[0058] 2.4 In order to explore the interaction mechanism between ZnO-CTS, density functional theory (DFT) simulation calculations were carried out.

[0059] In the mechanism exploration, Guassian 09 software was used for density functional simulation calculations, in which the ground state used the B3LYP exchange-correlation hybrid functional method. The (ZnO) 3 Small clusters are used to represent ZnO crystals. The CTS molecule is simplified and replaced by the fragment shown in Formula I, and the CTS molecule is constructed using the 6-311g (d, p) basis set. To explore the interaction between ZnO and CTS groups, ZnO clusters are placed near different functional groups of the CTS molecule, and the binding energy is calculated according to the following formula:

[0060] ΔE m =E total -(E CTS +E ZnO )

[0061] Among them, E total Refers to the total energy of the ZnO-CTS complex, E CTS and E ZnO They refer to the energies before CTS and ZnO combination, respectively.

[0062] like Figure 5 As shown, the CTS molecule is represented by a repeating unit fragment, and ZnO is represented by (ZnO) 3 Cluster structure representation. ZnO cluster model placed in different functional groups (-OH, -NH 2 ,-CO-), and then the structure was optimized. The optimized configuration and calculated binding energy are shown in Figure 5 The results show that ZnO and -NH 2 The binding energy between the groups is the lowest, indicating that the binding effect between the two plays a dominant role in the ZnO-CTS composite, which is consistent with the conclusion of the above infrared spectrum. 2 The advantages of the combination of groups and metal ions have also been demonstrated in our previous studies. Based on the large number of amine sites on the CTS molecule, ZnO can be anchored in the CTS gel framework, thereby growing uniformly and in a controlled manner.

[0063] Experimental Example 1

[0064] In the present invention, RhB is used as a representative organic pollutant, and its degradation effect is detected in the presence of ZnO and ZnO-CTS to characterize the photocatalytic properties of the two materials.

[0065] The specific method is to mix 5mL Zn(AC) 2 and Zn(AC) 2ZnO and ZnO-CTS gel prepared with CTS solution were put into 30 mL of Rhodamine B solution (c RhB =5mg / L) solution, stirred in a dark environment for 20 minutes, and then irradiated with simulated sunlight for 80 minutes. Samples were taken at regular intervals for UV / visible absorption spectrum detection. Figure 6 As shown in a and b, in a dark environment, the absorption spectrum of RhB in the solution with the addition of ZnO sample was almost unchanged, while the absorption spectrum of RhB in the solution with the addition of ZnO-CTS sample decreased slightly, indicating that the ZnO-CTS gel played an adsorption role. For both samples, the main changes in the absorbance of RhB occurred in the illumination stage, indicating that the decrease in its concentration was mainly caused by photocatalysis, and the adsorption process of the ZnO-CTS composite gel played a synergistic role with the photocatalytic process. After 80 minutes of illumination, the intensity of the characteristic peak (553nm) of RhB in the solution with the addition of ZnO-CTS was almost reduced to 0, which was much lower than that of the system with the addition of ZnO. Correspondingly, as shown in the inset in 6b, the solution with the presence of ZnO-CTS became almost transparent. Therefore, ZnO-CTS caused faster degradation of RhB than ZnO. The degradation curve over time and the corresponding kinetic fitting curve are shown in Figure 6b. Figure 6 c and d show more clearly the higher catalytic efficiency of ZnO-CTS. 0 / c) plotted against illumination time, and the fitting curve was more consistent with the linear relationship, indicating that the degradation process followed pseudo-first-order kinetics. According to the fitting curve, the apparent rate constants of ZnO-CTS and ZnO in the degradation process were 0.04min -1 and 0.03min -1 .

[0066] Example 3

[0067] In order to explore the mechanism of the improvement of the photocatalytic efficiency of ZnO-CTS samples, the luminescence properties of the samples were investigated, including UV / visible diffuse reflectance spectra and fluorescence emission spectra. Figure 7 As shown in a, the absorption shoulder of ZnO is located at 400nm, while the absorption shoulder of ZnO-CTS moves to a longer wavelength, indicating that ZnO-CTS has a stronger absorption capacity for visible light. Correspondingly, the band gaps of the two samples were calculated according to the Tauc Plot formula:

[0068] (αhν) 1 / m =B(hν-E g )

[0069] Among them, α is the light absorption coefficient (absorbance value is used here instead), h is Planck's constant, ν is the light frequency, B is the proportionality coefficient, E gis the band gap energy. The exponential coefficient m is related to the type of semiconductor. For the direct band gap semiconductor ZnO, it is taken as 1 / 2. As shown in the inset of 7a, with the parameter (αhv) 2 Plot hν and calculate the corresponding E according to the intersection of the tangent line and the X-axis g Compared with ZnO, the band gap energy of ZnO-CTS is lower, which means that ZnO-CTS is more easily excited by light and can make better use of light. Take a certain amount of powder sample to make a dispersion with a certain concentration, and detect its fluorescence emission spectrum, such as Figure 7 As shown in Figure b. The fluorescence intensity of ZnO-CTS is weaker than that of ZnO, which indicates that the electron-hole recombination behavior that causes the fluorescence phenomenon in the ZnO-CTS system is weakened. Reducing the electron-hole recombination behavior is beneficial to improving the photocatalytic efficiency, thereby improving the catalytic degradation efficiency of ZnO-CTS on RhB. The above excellent light utilization performance of ZnO-CTS may come from the passivation effect of the CTS functional group on the particle surface.

[0070] Experimental Example 2

[0071] As described in Example 3, the addition of CTS in the ZnO synthesis process improves the photocatalytic degradation performance. In order to obtain the optimal catalytic efficiency, we conducted a controlled variable control experiment to explore the effects of the concentration and volume ratio of the prepared precursor on the catalytic degradation effect. The experimental condition control variables are shown in Table 1.

[0072] Table 1 Experimental conditions control in control experiment

[0073]

[0074] After ZnO-CTS was prepared under different conditions, the material was put into RhB solution for light degradation test according to the degradation experimental steps in Experimental Example 1. The change of RhB residue over time was detected by monitoring the ratio of the characteristic UV-visible absorption peak of RhB at 553nm to the initial value, such as Figure 8 As shown in the figure. As the Zn ion concentration increases, the concentration of RhB in the degradation process decreases in the first 20 minutes and then tends to be consistent. It can be seen that the increase in Zn ion concentration has little effect on the catalytic degradation efficiency of ZnO-CTS. However, as the Zn ion concentration increases, the product gradually becomes turbid, as shown in the figure. Figure 8 As shown in Figure a, this is because the higher Zn ion concentration causes it to react with NaOH on the surface of the gel sphere too quickly and not be fixed in the gel in time. In subsequent experiments, the Zn ion concentration was maintained at 0.1 mol / L. Figure 8 b shows the effect of NaOH concentration on the degradation efficiency of the product ZnO-CTS. The degradation efficiency of the product prepared under low concentration 0.2 mol / L NaOH conditions is faster. Figure 8c shows the effect of the volume ratio of the two precursor solutions NaOH and CTS-Zn mixed solution on the catalytic efficiency of the product. NaOH :V CTS-Zn =4:1,5:1) caused a faster degradation of RhB. This may be related to the simultaneous participation of NaOH in gelation and ZnO formation. In order to obtain products with higher catalytic efficiency, the amount of NaOH should be controlled in an appropriate range, avoiding contact with excessive concentration of dripping CTS-Zn solution, while providing sufficient amount to meet the requirements of gelation and ZnO formation.

[0075] Different from Zn 2+ The concentration of NaOH has a slight effect on the photocatalytic efficiency of the product, while the concentration of CTS has a significant effect on the photocatalytic efficiency of the product. Figure 8 As shown in Figure d, with the increase of the concentration of gelling agent CTS, the degradation rate of RhB catalyzed by ZnO-CTS slowed down. It seems that the larger degree of gelation weakened the photocatalytic efficiency of the prepared ZnO-CTS. In order to explore the reason, the surface morphology of the ZnO-CTS gel spheres was observed by AFM after freeze-drying. Fig. 9 As shown in the figure, pore structure was observed on the surface of the gel, and the pore size decreased with the increase of CTS concentration. Therefore, in the process of preparing ZnO-CTS, when the CTS-Zn mixed solution was dropped into NaOH, the excessively high CTS concentration led to too fast gelation, which caused NaOH to diffuse into the gel and ZnO. 2+ The diffusion rate and contact amount of the reaction are reduced. In summary, during the preparation of ZnO-CTS, the concentration and addition amount of the precursor should be controlled within an appropriate range to maximize the regulatory role of the CTS gel framework in the ZnO growth process.

[0076] Experimental Example 3

[0077] In this experimental example, RhB was used as a representative organic pollutant, and its degradation effect was detected in the presence of the ZnO-CTS gel prepared in Example 1 and the ZnO-CTS flocs prepared in Comparative Example 2 to characterize the photocatalytic performance of the two materials.

[0078] The specific method is to prepare 10mL Zn(AC) 2 ZnO-CTS gel and ZnO-CTS flocs prepared from CTS solution were put into 50 mL of Rhodamine B solution (c RhB =5mg / L) solution, stirred in a dark environment for 10 minutes, and then irradiated with simulated sunlight for 80 minutes. Samples were taken at regular intervals for UV / visible absorption spectrum detection. The results were as follows Fig.10 shown.

[0079] After adding the two samples, the main changes in the absorbance of RhB appeared in the illumination stage, indicating that the decrease in its concentration was mainly caused by photocatalysis. After 80 minutes of illumination, the intensity of the characteristic peak (553nm) of RhB in the solution with the addition of ZnO-CTS gel was almost reduced to 0, which was much lower than that of the system with the addition of ZnO-CTS flocs. Therefore, ZnO-CTS gel caused faster degradation of RhB than ZnO-CTS flocs. The degradation curve over time and the corresponding kinetic fitting curve are shown in Figure 2. Fig.10 As shown in c and d, the higher catalytic efficiency of ZnO-CTS is more clearly shown. 0 / c) plotted against illumination time, and the fitting curve was more consistent with the linear relationship, indicating that the degradation process followed pseudo-first-order kinetics. According to the fitting curve, the apparent rate constants corresponding to ZnO-CTS gel and ZnO-CTS flocs in the degradation process were 0.04min -1 and 0.02min -1 .

[0080] In the present invention, a new environmentally friendly ZnO-CTS catalyst system was innovatively developed based on the natural polysaccharide chitosan, and its application in sewage treatment was explored. Due to the abundant reserves of chitosan in nature and its bio-friendly characteristics, the use of chitosan in the preparation process of ZnO materials provides a new environmentally friendly synthesis route for the synthesis of photocatalysts. Compared with the ZnO material synthesized by the ordinary hydrothermal method, the ZnO-CTS material synthesized by the present invention shows more excellent photocatalytic performance. Combining experimental and theoretical simulation analysis, the mechanism of improving the photocatalytic efficiency of the material is revealed. During the preparation process, the -NH 2 The groups act as anchoring sites for Zn ions, effectively causing the controlled growth and surface passivation of ZnO, thereby promoting the efficiency of photocatalytic conversion. In addition, the effects of precursor concentration and addition amount on the photocatalytic performance of the prepared ZnO-CTS were further explored through control experiments, and the optimal experimental conditions were summarized. This study is expected to provide reference significance for the synthesis of high-catalytic photocatalysts and the greening of water pollution treatment.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A photocatalytic hydrogel based on zinc oxide-chitosan, characterized in that: The photocatalytic hydrogel takes chitosan gel as a substrate and is loaded with ZnO nanoparticles.

2. The photocatalytic hydrogel according to claim 1, characterized in that The size of the ZnO nanoparticles is 2-4 nm.

3. The method for preparing the photocatalytic hydrogel according to any one of claims 1 to 2, characterized in that: include: The zinc salt is dissolved in a chitosan aqueous solution, the mixed solution is added into an alkaline solution, and the mixture is heated for reaction to obtain a zinc oxide-chitosan based photocatalytic hydrogel.

4. The preparation method according to claim 3, characterized in that: The zinc salt includes Zn(CH3COO)2.

5. The preparation method according to claim 3, characterized in that: The concentration of chitosan in the chitosan aqueous solution is 1-2 wt%, preferably 1 wt%.

6. The preparation method according to claim 3, characterized in that: The concentration of the zinc salt in the mixed solution is 0.1-0.4 mol / L, preferably 0.1 mol / L.

7. The preparation method according to claim 3, characterized in that: The alkali solution includes NaOH solution; Preferably, the concentration of the NaOH solution is 0.2 to 0.4 mol / L, preferably 0.2 mol / L; More preferably, the volume ratio of the NaOH solution to the mixed solution is 2:1 to 5:1, preferably 4:1 or 5:

1.

8. The preparation method according to claim 3, characterized in that: The temperature of the heating reaction is 95-105° C., preferably 100° C.; the time of the heating reaction is 1-2 h, preferably 1 h.

9. Use of the photocatalytic hydrogel according to any one of claims 1 to 2 and / or the photocatalytic hydrogel prepared by the preparation method according to any one of claims 3 to 8 in photocatalytic degradation and removal of organic pollutants in water.

10. The use according to claim 9, characterized in that The organic pollutants include organic dyes, and the organic dyes include Rhodamine B.

Citation Information

Cited By

  • Preparation method of photocatalytic adsorption material

    CN120984246A